Innovation policy and performance a cross-country comparison. (Science and innovation., 2005)
This publication examines the relationship between innovation policy and economic performance in six OECD countries. In-depth analyses highlight countries' strengths and weaknesses in innovation, as well as the effectiveness of their innovation policies in driving economic performance. Taken together, the country studies indicate that countries share a need to adapt, or even profoundly change, their innovation policies in order to deal with opportunities and threats posed by new technological and economic developments.--Publisher's description.